Clinical application of bone turnover markers in treating osteoporotic vertebral compression fractures and their role in predicting fracture progression. Issue 32 (12th August 2022) - Han, Moon-Soo; Lee, Gwang-Jun; Lee, Seul-Kee; Lee, Jung-Kil; Moon, Bong Ju
Abstract : This study aimed to investigate whether changes in the bone turnover markers (BTMs) during teriparatide therapy for osteoporotic vertebral compression fractures could reflect therapeutic effects by analyzing the relationship between clinical and radiological features and BTMs. A total of 33 patients with 51 osteoporotic vertebral compression fracture segments were included. Plain radiographs and BTM levels were evaluated at the pretreatment and at 3 months after teriparatide treatment. Based on serial vertebral compression ratio analysis, the progression of fracture was defined as a vertebral compression ratio decrease of ≥10%, relative to the pretreatment values. All segments were divided into 2 groups: the "maintain" group with 32 (62.7%) segments and the "progression" group with 19 (37.3%) segments. After the teriparatide treatment, serum osteocalcin and serum C-terminal telopeptide of type I collagen levels ( P = .028 and .008, respectively), and change amounts of them were significantly larger, increasing ( P = .001) in the progression group. The vitamin D (25OH-D) levels were significantly lower ( P = .038) in the progression group; however, the relative changes in the 25OH-D levels between the 2 groups, before and after the treatment, were not significantly different ( P = .077). The parathyroid hormone (PTH) levels were reduced by the teriparatide treatment in both groups, while the decrease in PTH concentration after the treatment was significantly more pronounced in the progression group ( P = .006). Significant increase in the osteocalcin and serum C-terminal telopeptide of type I collagen levels and a simultaneous decrease in the PTH levels during the teriparatide treatment suggest that clinicians should assume the progression of fracture.